Regulation of Tertiary Education Institutions in Botswana: Issues and Options - Samboma, Thabile Anita (Advances in Social Sciences Research Journal, 2017)
The Government of Botswana has, and continues to invest on tertiary education as the key driver to knowledge based society. Tertiary institutions have been entrusted with the provision of quality and relevant education. Regulation of tertiary institutions has become a global issue of concern mainly due to the pressures of stakeholder's needs and expectations. This paper therefore, raises practical issues that affect governance and regulation of tertiary institutions. This study therefore, uses a desk-top approach, which relies heavily on secondary data from relevant sources and documentations related to issues on tertiary education in Botswana, in order to identify the challenges facing the tertiary education sector and come up with key policy implications and options to address the challenges. The paper observes that challenges do exist in tertiary institutions. One of the main challenges is fragmentation of regulatory bodies, and this has negatively impacted on education access, quality and relevance. This paper also proposes options to improve the tertiary education sector. It is therefore, vital that over sight institutions like Botswana Qualification Authority (BQA) and Human Resource Development Council (HRDC) ensure that the country's vision 2036 is realised. The paper proposes that a university act should be put in place to govern all universities and an independent Quality Assurance monitoring mechanism which will serve as an instrument to regulate universities.